A genome-wide association study identifies nucleotide variants at SIGLEC5 and DEFA1A3 as risk loci for periodontitis - DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2017)
Periodontitis is one of the most common inflammatory diseases, with a prevalence of 11% worldwide for the severe forms and an estimated heritability of 50%. The disease is characterized by destruction of the alveolar bone due to an aberrant host inflammatory response to a dysbiotic oral microbiome. Previous genome-wide association studies (GWAS) have reported several suggestive susceptibility loci. Here, we conducted a GWAS using a German and Dutch case-control sample of aggressive periodontitis (AgP, 896 cases, 7,104 controls), a rare but highly severe and early-onset form of periodontitis, validated the associations in a German sample of severe forms of the more moderate phenotype chronic periodontitis (CP) (993 cases, 1,419 controls). Positive findings were replicated in a Turkish sample of AgP (223 cases, 564 controls). A locus at SIGLEC5 (sialic acid binding Ig-like lectin 5) and a chromosomal region downstream of the DEFA1A3 locus (defensin alpha 1-3) showed association with both disease phenotypes and were associated with periodontitis at a genome-wide significance level in the pooled samples, with P = 1.09E-08 (rs4284742,-G; OR = 1.34, 95% CI = 1.21-1.48) and P = 5.48E-10 (rs2738058,-T; OR = 1.28, 95% CI = 1.18-1.38), respectively. SIGLEC5 is expressed in various myeloid immune cells and classified as an inhibitory receptor with the potential tomediate tyrosine phosphatases SHP-1/-2 dependent signaling. Alpha defensins are antimicrobial peptides with expression in neutrophils andmucosal surfaces and a role in phagocyte-mediated host defense. This study identifies the first shared genetic risk loci of AgP and CP with genome-wide significance and highlights the role of innate and adaptive immunity in the etiology of periodontitis.
Keywords: CORONARY-ARTERY-DISEASE; GENE COPY NUMBER; ALPHA-DEFENSIN; SUSCEPTIBILITY LOCUS; POPULATION; EXPRESSION; REGRESSION; PHENOTYPES; RATIONALE; RESOURCE